Pemberdayaan, Kompetensi dan Job Relevant Information terhadap Komitmen Organisasional dan Kinerja Pengelola Anggaran - Ni Made Wistriyanti; Ni Nyoman Sunariani (Universitas Pendidikan Nasional, 2017)
The purpose of this research is to determine the effectof Employee Empowerment, Human Resource Competency, Job Relevant Information of the Organizational Commitment and Performance of the Budget Administrator. This research is done on the local work unit district (SKPD) of Klungkung Regency, by taking a sample of 150 respondent. These samples were teken with disproportionate stratified random sampling technique, while data analysis techniques using Structural Equation Model (SEM) assisted with AMOS versi 22 program. The result showed that the effect of employee empowerment, Human Resource Competency, Job Relevant Information to the Organizational Commitment is significantly positives. Effects of employee empowerment, Human Resource Competency, Job Relevant Information to the Performance of the Budget is significantly positive. As well as the influence of Organizational Commitment to Performance of the Budget Administrator significant positive effect.